Urban Particulate Matter Impairment of Airway Surface Liquid–Mediated Coronavirus Inactivation. (3rd November 2021) - Stapleton, Emma M; Welch, Jennifer L; Ubeda, Erika A; Xiang, Jinhua; Zabner, Joseph; Thornell, Ian M; Nonnenmann, Matthew W; Stapleton, Jack T; Comellas, Alejandro P
Abstract: Air pollution particulate matter (PM) is associated with SARS-CoV-2 infection and severity, although mechanistic studies are lacking. We tested whether airway surface liquid (ASL) from primary human airway epithelial cells is antiviral against SARS-CoV-2 and human alphacoronavirus 229E (CoV-229E) (responsible for common colds), and whether PM (urban, indoor air pollution [IAP], volcanic ash) affected ASL antiviral activity. ASL inactivated SARS-CoV-2 and CoV-229E. Independently, urban PM also decreased SARS-CoV-2 and CoV-229E infection, and IAP PM decreased CoV-229E infection. However, in combination, urban PM impaired ASL's antiviral activity against both viruses, and the same effect occurred for IAP PM and ash against SARS-CoV-2, suggesting that PM may enhance SARS-CoV-2 infection. Abstract : Primary human airway surface liquid (ASL) inactivates severe acute respiratory syndrome coronavirus 2 and human alphacoronavirus coronavirus 229E in vitro. Air pollution particulate matter (PM) inhibits ASL viral inactivation, suggesting PM may enhance coronavirus infection by impairing airway innate immunity.